Geotechnical damage due to the 2016 Kumamoto Earthquake and future challenges - H. Hazarika; T. Kokusho; R.E. Kayen; S. Dashti; H. Fukuoka; T. Ishizawa; Y. Kochi; D. Matsumoto; H. Furuichi; T. Hirose; T. Fujishiro; K. Okamoto; M. Tajiri; M. Fukuda (International Association of Lowland Technology, 2017)
The 2016 Kumamoto earthquake with a moment magnitude of 7.0 (Japanese intensity = 7) that struck on April 16 brought devastation in many areas of Kumamoto Prefecture and partly in Oita Prefecture in Kyushu Region, Japan. The earthquake preceded a foreshock of magnitude 6.5 (Japanese intensity = 7) on April 14. This paper summarizes the damage brought to geotechnical structures by the two consecutive earthquakes within a span of twenty-eight hours. The paper highlighted some of the observed damage and identifies reasons for such damage. The geotechnical challenges towards mitigation of losses from such earthquakes are also suggested.